(untitled) (Revista de Artes Marciales Asiáticas, 2012)
Rooted in the author’s field experience studying the traditional South Indian martial art kalarippayattu, this article examines the complexities of communication, including the use of touch as a teaching tool, in an intercultural teacher-student relationship, and surfaces how gender, culture, and class impacted learning in this embodied art form.